Wyznaczanie mierników perspektywy klienta z wykorzystaniem arkusza kalkulacyjnego Excel - Kes, Zdzisław (Choosing Measures for the Customer Perspective Using Excel Sheet for Calculating, 2008)
The paper shows capability of utilization Excel in controlling. In this purpose presented constructions four meters included in prospect of client of Balancscore Card. Described meters have been taken advantage on building of application enabling scaling and translation of malingering on supplied data. Construction of this application is based on environment of imputed sheet Excel.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (6); 2008; nr 1196, s. 48-66